The Comparative Immunological Characteristics of SARS-CoV, MERS-CoV, and SARS-CoV-2 Coronavirus Infections - Zhang, Yun-yu; Li, Bi-ru; Ning, Bo-tao (Frontiers in Immunology, 2020)
：Immune dysfunction and aberrant cytokine storm often lead to rapid exacerbation in late stages SARS-CoV and MERS-CoV patients. However, its underlying immunopathology mechanism were not fully understood and research regarding development of vaccine, anti-viral drugs and immunotherapy were making little progress. The newly discovered 2019-nCoV marked the third coronavirus pandemic in human population, with enhanced pathogenicity and transmissibility. It’s highly genetic homologous to SARS-CoV and could lead to similar clinical disease named COVID-19. In this review, we provide detailed knowledge about the pathogenesis and immunological characteristics of SARS and MERS, as well as recent findings regarding clinical features and potential pathogenesis of COVID-19. Host Immunological characteristics were finally compared between the 3 types of coronavirus diseases. We aimed to provide insights and scientific evidences in discovering the pathogenesis and therapeutic strategies of COVID-19.